6(2n-1)=(8n+5)+4

Simple and best practice solution for 6(2n-1)=(8n+5)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2n-1)=(8n+5)+4 equation:


6(2n-1)=(8n+5)+4

We simplify the equation to the form, which is simple to understand
6(2n-1)=(8n+5)+4

Reorder the terms in parentheses
+(+12n-6)=(8n+5)+4

Remove unnecessary parentheses
+12n-6=+(+8n+5+)+4

Remove unnecessary parentheses
+12n-6=8n+5+4

We move all terms containing n to the left and all other terms to the right.
+12n-8n=+5+4+6

We simplify left and right side of the equation.
+4n=+15

We divide both sides of the equation by 4 to get n.
n=3.75

See similar equations:

| x^22+21x+110=0 | | 6x^2-24x+16=-2 | | -56=8y | | 8(3n-4)=(2n+9)+5 | | 35x^2-8x-16=0 | | 35x^2+14x+7=0 | | (y-7)(y-7)+y^2=(y+7)(y+7) | | (3a+b)(-2b+a)= | | -2(t-2)+6t=8t-9 | | 3x+x=100 | | 2x(x+6)=(x+1)(x+6) | | 0.6(3x+6)=1.4-(x+2) | | 6+2b=1+1b | | 3x^2+19x+16=0 | | x^2+50x+400=0 | | 8(y-3)/5=-2y | | 3(3+5d)+4(10d+7)= | | 6-2(a-1)=5+a | | -7(x+4)-4=-32 | | 4x+7x=10.5x+14 | | 4x+7x=10.5+14 | | 2(3+5)-9= | | -9w=12 | | x^2=.8333333x-.166666667 | | -3(t-6)-(t+7)=7 | | 15x-9=50x+19 | | .05x+.04(15000-x)=680 | | -6.5=-x+[-8.5] | | m=3m+3u | | -4+2=-3(2y+2) | | -(-4x+8y-5)= | | 0.30x+.05(10-x)=.10(-20) |

Equations solver categories